Mechanism of CO2 Capacity Reduction of Flexible Metal-Organic Framework Caused by Water Adsorption - Watanabe, Satoshi; Hiraide, Shotaro; Kunimitsu, Hayato; Fujiwara, Atsushi; Miyahara, Minoru T. (Frontiers in Materials, 2022)
Elastic layer-structured metal-organic framework (MOF)-11 (ELM-11: [Cu(BF4)2(4,4’-bipyridine)2]), which is a crystalline porous material, is a promising adsorbent for high-throughput and high-efficiency separation processes of CO2 because of its peculiar adsorption characteristics originating from the flexibility of the crystal framework. However, the exposure of ELM-11 to water vapor has been reported to reduce its CO2 capacity, which is problematic for processing feed gases that contain a certain concentration of water vapor. In this study, we investigated the stability of ELM-11 against water vapor exposure to reveal the mechanism of CO2 capacity reduction. Our combined measurements of adsorption isotherms and X-ray diffraction patterns indicated that the CO2 capacity reduction was caused by the partial formation of a crystalline subphase upon adsorption of water molecules and the subsequent formation of an amorphous phase to relax the crystalline grain boundaries. Because a higher supply rate of water molecules resulted in a larger amount of subphase formation, we concluded that the structural subphase was a metastable kinetically controlled structure, formed through the rate-dependent adsorption of water molecules. These results suggest that slowing the adsorption rate is an effective approach to suppress the formation of the subphase; therefore, we proposed the covering of ELM-11 surfaces with porous shells. We used ELM-12 ([Cu(CF3SO3)2(4,4’-bipyridine)2]) as a shell material because of its robust stability against water adsorption and affinity with ELM-11. The ELM-12 shell decreased the adsorption rate of water molecules compared with that of bare ELM-11, resulting in the suppression of subphase formation and preventing CO2 capacity reduction. Although further optimization of the shell thickness and coverage is required to keep the capacity completely unchanged, controlling the adsorption rate of water molecules is successfully demonstrated to be possible with shell formation, which is key for industrial applications of ELM-11.